Association between Life’s Crucial 9 and metabolic dysfunction-associated steatotic liver disease: the mediating role of neutrophil-percentage-to-albumin ratio - Zhu, Na; Li, Yanyan; Lin, Yingying; Cui, XinYu; Li, Xin (Frontiers in Nutrition, 2025)
BackgroundThe development of metabolic dysfunction-associated steatotic liver disease (MASLD) is closely associated with cardiovascular health (CVH) status and chronic inflammation. Life’s Crucial 9 (LC9) is the most recent index to assess CVH; its association with MASLD and liver fibrosis is unclear. This study aimed to investigate the association of LC9 with MASLD and hepatic fibrosis and to reveal for the first time the mediating role of a novel inflammatory marker, neutrophil percentage-to-albumin ratio (NPAR), in the association between LC9 and MASLD.MethodsThis study was a cross-sectional analysis of data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. The United States Fatty Liver Index (US-FLI) ≥ 30 was used to diagnose MASLD, and liver stiffness measurement (LSM) > 8.2 is defined as liver fibrosis. Weighted multifactorial regression, restricted cubic spline analysis (RCS), and subgroup analyses were used to assess the association between LC9 and MASLD and liver fibrosis. Mediation analysis was used to explore the possible mediating role of NPAR in the association of LC9 with MASLD.ResultsA total of 9,623 participants were included in this study. After adjusting for all confounders, LC9 was significantly and negatively associated with both MASLD (OR = 0.59, 95% CI: 0.54–0.64) and hepatic fibrosis (OR = 0.66, 95% CI: 0.45–0.97), with each 10-point increase in the LC9 score decreasing the prevalence by 41% and 34%, respectively. In subgroup analyses, interaction tests showed that age, education, deprivation, obesity, smoking, hypertension, diabetes, and hyperlipidemia significantly affected the association between LC9 and MASLD (P for interaction < 0.05). In addition, NPAR was positively associated with the prevalence of MASLD, with a 5% increase in the prevalence of MASLD for each unit increase in NPAR (OR = 1.05, 95% CI: 1.01–1.09). The positive association between NPAR and MASLD was stronger in younger age groups (<60 years), non-drinkers, and participants without diabetes or hyperlipidemia. Mediation analysis showed that NPAR mediated 2.84% of the association between LC9 and MASLD (p < 0.001).ConclusionGood CVH status (high LC9 score) was associated with lower prevalence of MASLD and liver fibrosis, and NPAR partially mediated the association between LC9 and MASLD. This study provides new epidemiological evidence for preventing MASLD by improving CVH and inflammatory modulation.